Pemanfaatan Strategi Omnichannel dalam Transformasi Digital Marketing PT. Yakult Indonesia Persada - Raihan Maulana, Adi Artanta; Zaky, Afif Amar; Magfiroh, Ayuk; Diva, Marcellina Mutiara; Pratama, Randy; Riyono Riyono (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The development of digital technology has driven a significant transformation in the company's marketing strategy, including in the health beverage sector. This study aims to examine the use of omnichannel strategies in supporting digital marketing in PT. Yakult Indonesia Persada. The method used is descriptive observation with a focus on the integration of digital marketing channels and traditional distribution. The results show that the implementation of an omnichannel strategy is able to create a consistent consumer experience, expand market reach, and strengthen brand image. The integration between digital channels such as social media and e-commerce with conventional distribution through Yakult Lady provides more flexible product access for consumers. In addition, educational and informative digital content has proven to be effective in increasing public health awareness and customer loyalty. However, challenges such as cross-channel information consistency and integrated technology management still need to be addressed. This study concludes that omnichannel strategy is a relevant and adaptive approach in dealing with the dynamics of the health beverage industry in the digital era. The implementation of this strategy not only supports operational efficiency, but also strengthens the relationship between the company and consumers through a personalized and sustainable experience. These findings are expected to serve as a reference for other companies in designing digital marketing strategies that are inclusive and responsive to changing consumer behavior.